2017
DOI: 10.1159/000468146
|View full text |Cite
|
Sign up to set email alerts
|

Lower Visual Avoidance in Dementia Patients Is Associated with Greater Psychological Distress in Caregivers

Abstract: Caring for a spouse with dementia can lead to increased health problems in caregivers. The present study examined whether patient deficits in visual avoidance, a common form of emotion regulation, are related to greater psychological distress in caregivers. Participants were 43 Alzheimer disease (AD) patients, 43 behavioral variant frontotemporal dementia (bvFTD) patients, and their spousal caregivers. Patient visual avoidance (e.g., gaze aversion) was measured using behavioral coding of head, body, and eye po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 56 publications
1
17
0
Order By: Relevance
“…Given the increasing rates of neurodegenerative diseases and associated caregiving, there is an urgent need to identify particular factors that influence vulnerability to the negative effects of caregiving. Aggregating the present findings with our previous findings on the association between visual avoidance in patients and mental health in caregivers [11], we suggest that a comprehensive (e.g., emotion reactivity, regulation, and recognition) and detailed (e.g., target and non-target emotions) assessment of patient emotional functioning will be helpful in developing a more complete understanding of associations between particular patient behaviors and particular adverse caregiver outcomes, which may benefit both the caregivers and patients [4]. …”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Given the increasing rates of neurodegenerative diseases and associated caregiving, there is an urgent need to identify particular factors that influence vulnerability to the negative effects of caregiving. Aggregating the present findings with our previous findings on the association between visual avoidance in patients and mental health in caregivers [11], we suggest that a comprehensive (e.g., emotion reactivity, regulation, and recognition) and detailed (e.g., target and non-target emotions) assessment of patient emotional functioning will be helpful in developing a more complete understanding of associations between particular patient behaviors and particular adverse caregiver outcomes, which may benefit both the caregivers and patients [4]. …”
Section: Resultssupporting
confidence: 86%
“…In our own work, we have found that neurodegenerative diseases can produce profound changes in patients’ emotional behavior, including alterations in reactivity (generating emotional responses [8]), regulation (adjusting emotional responses [9]), and recognition (identifying emotions in others [10]). Importantly, we have found that deficits in patients’ emotional functioning (i.e., less frequent use of visual avoidance from negative stimuli – a specific type of emotion dysregulation) are associated with adverse outcomes in caregivers (e.g., greater psychological distress [11]). In the present study, we examine the impact of deficits in patient emotional reactivity on caregiver well-being, with a particular focus on subjective emotional experience.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, many studies have consistently demonstrated that patients with bvFTD have marked difficulties with emotion recognition, which is critical for successful social interactions (20)(21)(22). Patients with bvFTD also have deficits in emotion regulation that are associated with the psychological distress of their caregivers (23). The inability of patients with bvFTD to read or regulate emotions results in misunderstanding meaning in situations and responding empathically (6).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, attentional deficits have been linked with decreases in quality of life in patients with dementia, highlighting the real-world consequences of abnormal attentional processing (Lawson et al, 2016). Focusing on visual avoidance per say, prior research from our group has linked deficits in visual avoidance among patients with behavioral variant frontotemporal dementia (bvFTD) and Alzheimer's disease (AD) with greater psychological distress in spousal caregivers (Otero and Levenson, 2017), which is consistent with the important role that emotion regulation plays in interpersonal contexts.…”
Section: Neurodegenerative Disease As a Model For Studying Visual Avomentioning
confidence: 99%